Dose selection for biological enzyme replacement therapy indicated for inborn errors of metabolism - Yuen Yi Hon; Jie Wang; Henrietta Abodakpi; Anand Balakrishnan; Michael Pacanowski; Sushanta Chakder; Patroula Smpokou; Kathleen Donohue; Yow‐Ming C. Wang (Wiley, 2023)
Abstract This paper summarizes key features of the dose‐finding strategies used in the development of 11 approved new molecular entities that are first‐in‐class enzyme replacement therapy (ERT), with a goal to gain insight into the dose exploration approaches to inform efficient dose‐finding in future development of biological products for Inborn Errors of Metabolism (IEM). Dose exploration should preferably begin in in vitro studies, followed by testing multiple doses in an appropriate animal disease model, when available, which can provide important information for dose assessment in humans. Performing adequate dose‐finding in early phase clinical studies in a well‐defined study population, including pediatric subjects, is generally critical to inform dose selection for pivotal trials; alternatively, additional dose exploration can be incorporated as part of a pivotal trial. Two important considerations for successful dose selection include (1) identifying appropriate disease‐specific endpoints, including pharmacodynamic (PD) end points and intermediate clinical end points or clinical end points, and (2) designing a study with adequate treatment durations for evaluating these end points. Appropriately selected PD biomarkers is useful for dose selection, and early development of these biomarkers can facilitate the overall clinical development program. Optimization of ERT doses, as well as evaluations of patient intrinsic factors and/or immune tolerance strategies may be necessary to overcome antibody responses or increase efficacy in IEM.